2019
DOI: 10.1002/er.4365
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol steam reforming on Ni/CaO catalysts for coproduction of hydrogen and carbon nanotubes

Abstract: Summary Catalytic steam reforming of ethanol is considered as a promising technology for producing H2 in the modern world. In this study, using a fixed‐bed reactor, steam reforming of ethanol was performed for production of carbon nanotubes (CNTs) and H2 simultaneously at 600°C on Ni/CaO catalysts. Commercial CaO and a synthetic CaO prepared using sol‐gel were scrutinized for ethanol's catalytic steam reforming. Analysis results of N2 isothermal adsorption indicate that the CaO synthesized by sol‐gel has more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
(76 reference statements)
1
22
0
Order By: Relevance
“…However, biomass is considered as a promising renewable energy source. 8,9 Furthermore, activated carbon can be prepared from various feedstocks, including coal, blue-coke, and organic materials. 2,3 Activated carbon is carbonaceous material containing developed internal pore structure with high specific surface area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, biomass is considered as a promising renewable energy source. 8,9 Furthermore, activated carbon can be prepared from various feedstocks, including coal, blue-coke, and organic materials. 2,3 Activated carbon is carbonaceous material containing developed internal pore structure with high specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] And it can be applied as catalyst support. 8,9 Furthermore, activated carbon can be prepared from various feedstocks, including coal, blue-coke, and organic materials. [10][11][12] Biomass is an ideal feedstock to prepare high specific surface area activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The second oxidation peaks appeared at about 500°C is related to oxidation of filamentous carbons such as carbon nanotubes (CNTs) and the result is consistent with SEM image in Figure C, D. Compared with Ni/AB‐2 catalyst, the mass loss of Ni‐Ce/AB‐2 catalyst during before and after reaction is less than fresh Ni‐Ce/AB‐2 catalyst, which indicated that the addition of Ce can reduce the generation of amorphous carbon during the reaction and promote the formation of filamentous carbon. It is reported that amorphous carbons are prone to encapsulate active catalytic sites, resulting in the deactivation of catalyst . The reduction of amorphous carbon deposition is beneficial to the improvement of catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Reforming gaseous products were measured by an infrared syngas analyzer (ETG, Italy) which could detect the gas concentration (vol%) of H 2 , CO, CO 2 , CH 4 , N 2 online with a sampling interval of 1 second. The detailed calculation method for the molar flow of the produced gas (mmol/min) has been presented in our previous work …”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, hydrogen as energy carrier is the most attractive because of its high calorific value and zero pollution. 1 Hydrocarbon and its derivatives, such as methane/natural gas [2][3][4][5][6] and alcohol/organic acid [7][8][9][10][11][12][13] steam reforming has been employed for hydrogen production for the high conversion efficiency of this process. Long-chain hydrocarbon fuels, [14][15][16][17] such as ndodecane, have widely used as hydrogen source since their high density, high hydrogen yield and good transportability.…”
Section: Introductionmentioning
confidence: 99%